2021
DOI: 10.1109/access.2021.3130270
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain-Based BIM Digital Project Management Mechanism Research

Abstract: The construction industry lacks a comprehensive and overall scheme for the use and management of building information modeling (BIM) in the whole building life cycle, especially the use of BIM technology for asset management and facility management. However, there is little understanding and implementation of enterprise BIM. BIM influences and changes the new project management mode of the whole life cycle of construction projects from design to construction. The safety, audit, responsibility and value of BIM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…It is implemented in the PhpStorm environment using the following tools: PHP, JavaScript, CSS, HTML. The application has an intuitive interface and consists of six sections, the main of which are: "Data Extraction", "Database", "Multivariate Analysis" and "Verification" [7].…”
Section: Materials and Research Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is implemented in the PhpStorm environment using the following tools: PHP, JavaScript, CSS, HTML. The application has an intuitive interface and consists of six sections, the main of which are: "Data Extraction", "Database", "Multivariate Analysis" and "Verification" [7].…”
Section: Materials and Research Methodsmentioning
confidence: 99%
“…Unlike the industrial society, in which the main activity was the production of material goods, in the current, post-industrial society, the main activity is the production of information (by information we mean knowledge as information about persons, objects, facts, events, phenomena and processes, regardless of the form their representation, which can be recorded on a material medium), and this process is called informatization (hence the term -information society). Such a shift in emphasis is caused, firstly, by the fact that humanity is aware of the limited natural resources of its habitat, and secondly, the emergence of global problems (for example, energy, environmental), the solution of which is impossible by the same means [7]. Information becomes the main resource for the development of the world community and significantly affects the development of other industries and spheres of life: science, technology, social spheres (cultural communication between people, education).…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Although the review did not yield many results in procurement, some overlays can be observed with supply chain management applications. Not only is blockchain used in procurement, but it also finds applications in material scheduling and tracking [100,101]. Blockchain-based procurement bidding systems can be used to ensure the quality of suppliers' materials while also providing the confidentiality needed in the bidding process [70,102].…”
Section: Procurement and Supply Chain Managementmentioning
confidence: 99%
“…Currently, these changes are the successful application of cloud technologies, so project activities are moving to complete independence from the geographical or technological location of project participants. The issue of digitalization of project management is considered in many works [3][4][5][6][7][8]. [3] states that companies that do not have an existing digital transformation program have a year or less to adopt it.…”
Section: References Analysis and Problem Statementmentioning
confidence: 99%
“…92 % of businesses believe that intelligent automation (combined use of artificial intelligence and automation) will be more widely used within their company over the next 12 months [5]. The benefits of digital transformation efforts include increasing market share (41 %), increasing customer interest in digital channels (37 %), more positive employee morale (37 %), greater activity on the Internet and mobile devices (32 %), income (30 %) [6]. An example of modern research is the work [7].…”
Section: References Analysis and Problem Statementmentioning
confidence: 99%